Methods and perspectives of geoarchaelogical site catchment analysis: identification of palaeoclimate indicators in the Oder region from the Iron to Middle Ages - Volkmann, Armin (Digital geoarchaeology, 2018)
In the last years, site catchment analyses came under criticism and were only used rarely in the geoarchaeological studies. It was assumed something like an eco-determinism, which most often did not consider a lack of free decision-making when choosing a new location for a new settlement. But it cannot be stated that prehistoric settlers were not affected by the geoecological potential given by their surrounding environment and that they chose settlement sites according to it. The more a prehistoric culture was based on agriculture and stock farming, the stronger was their dependency on geoecological site factors in the settlement region. New studies with an extended application of the site catchment analyses illustrate those relations very impressively. Therefore, it is essential to identify the prehistoric records, like the settlements belonging to an economic area, very accurately in order to evaluate the geoecological environment data. Different models can be applied in the geographic information systems (GIS) for the reconstruction of prehistoric surroundings that one wants to compare. In this way, it is possible to understand the human-environment interactions better in prehistoric settlement surroundings, and plausible thesis based upon a well-founded data basis can be verified or falsified as well.